Chapter 4.1 Professionalisation of Research Management and Administration in Southern Africa – A Case Study - Karin Dyason; Pamisha Pillay (Emerald Publishing Limited, 2023)
This case study will illustrate how the Southern African Research and Innovation Management Association (SARIMA) set in motion a professionalisation journey through close collaboration with its members while leveraging strategic partnerships and funding opportunities. The case study will highlight the impetus that inspired the journey, and the outputs aimed at accelerating the professionalisation of research management and administration (RMA) beyond Southern Africa.
10.1108/978-1-80382-701-820231026; 10.1108/978-1-80382-701-820231026; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262